Manfaat Intervensi Berbasis Digital Terapeutik terhadap Peningkatan Atensi dan Perilaku Regulasi Diri pada Anak ADHD - Lina Budiyarti; Nur Agustini; Imami Nur Rachmawati (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the benefits of digital-based interventions in influencing the function of attention and self-regulation in children with ADHD. The method used is a systematic review through the search for articles adapted to the formulation of research questions with the PICO formula in the Proquest, ScienceDirect and Scopus databases. The results showed that digital interventions based on the web, cellular and virtual reality applications designed according to the therapy requirements of ADHD children in the form of structured games, short stories, animated videos, scheduling and daily activity notes with several assignments to be completed were able to effectively increase attention/attention and improve self-regulatory behavior (emotions, planning and organizing) children with ADHD. In conclusion, intervention with digital therapy proved effective in increasing attention/attention and self-regulatory behavior in ADHD children. Keywords: ADHD, Attention, Digital Intervention, Self Regulation